2020
DOI: 10.1088/1757-899x/902/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of metal organic framework using succinic acid ligand with cobalt and iron metals as methylene blue dye adsorbent

Abstract: Metal-organic Framework (MOF) as a porous material has a potency for an organic dye adsorbent due to its tunable pore size. It can be a good candidate for selective separation of organic dye waste because of its organic functionality, high thermal and stability. In this study, MOF based on cobalt (Co) and iron (Fe) cations with succinic acid ligand was utilized for Methylene Blue (MB) removal from aqueous solution. Co-MOF and Fe-MOF were synthesized using solvothermal method at 120 °C for 20 h and characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Therefore, it is proposed that MB adsorption is confined on a monolayer and the adsorption sites are homogeneous. The adsorption of MB on the surface of Fe-MOF (succinic acid ligand) has also been studied in the past to fit the Langmuir model [26]. Whereas the Freundlich model concurs with the experimental findings on RhB adsorption.…”
Section: Dyesmentioning
confidence: 54%
See 3 more Smart Citations
“…Therefore, it is proposed that MB adsorption is confined on a monolayer and the adsorption sites are homogeneous. The adsorption of MB on the surface of Fe-MOF (succinic acid ligand) has also been studied in the past to fit the Langmuir model [26]. Whereas the Freundlich model concurs with the experimental findings on RhB adsorption.…”
Section: Dyesmentioning
confidence: 54%
“…Furthermore, it is suggested that the bond between both cationic dyes and the external area of MOF-88B(Fe) is not entirely a monolayer adsorption. A small number of heterogeneous adsorptions may also exist, and the driving force may come from chemical adsorption [26].…”
Section: Dyesmentioning
confidence: 99%
See 2 more Smart Citations
“…With some adjustments made in accordance with previous literature [ 27 ], the solvothermal method was utilized to synthesize Co-succinate [ 27 ]. In a combination of 50 mL N,N-dimethylformamide (DMF) and 2.5 mL DI solvents, approximately 1.5 mmol of the 1.71 g succinic acid ligand was dissolved.…”
Section: Methodsmentioning
confidence: 99%